The Mexican Tourism Sector as a Driver of Shared Growth - Aguilera, Nelly; Velázquez, César; Montesinos, Alejandro (World Bank, Washington, DC, 2013)
The goal of this paper is to estimate (with the data available) the impact of tourism as a factor of shared growth at the local or municipal level in Mexico. This country provides an excellent research example due to its socioeconomic characteristics, the fact that tourism is an important economic activity and that, in spite of not having an ideal database to prove empirically that tourism is associated to shared growth, there are reliable databases that combined may provide insightful information. The main findings are: first, tourist destinations in general have better economic conditions that neighbor communities. Second, in general we find that growth in tourism (growth in tourism related employment) is associated to more employment, to lower percentage of population working in social security, and to better figures in the Human Development Index (HDI). It has also been found that growth in maquila and oil industries do not present these positive impacts.